DESIGN AND FABRICATION OF SMART PARABOLIC TROUGH SOLAR FOOD DRYER (International Journal of Food and Nutritional Sciences, 2021)
Solar energy is renewable source of energy. Its uses do not contribute to emission of greenhouse gases and other pollutants to the environment. It is sustainable since it cannot be depleted in a time relevant to human race .it is a natural source of drying a food. So, it is always good for human health. It is also used for other applications in which heat is required in automobiles. Solar car in Japan features scope we are studying the temperature variation with respect to time. Heat energy is converted in electrical, mechanical, etc. by using concentrator. A parabolic trough concentrator is made of an aluminium sheet which is covered by a cloth on which rectangular mirror strips.